2016
DOI: 10.1016/j.compscitech.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Graded-permittivity polymer nanocomposites as superior dielectrics

Abstract: Materials exhibiting a gradient in permittivity are synthesized through the application of an external magnetic field to a suspension of Fe3O4@TiO2 nanoparticles in an epoxy matrix. It is shown how the application of the magnetic field not only induces the magnetophoretic motion of the particles, but causes also their alignment in high aspect ratio structures. The combination of these two effects gives rise to graded nanocomposites exhibiting gradients in permittivity that go beyond the ones predicted for nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Functional grading methods used in the literature for the fabrication of polymer composites and micro- and nanofillers are liquid-phase processing. Extrusion [ 105 , 106 ], infiltration [ 107 , 108 ], electrical deposition methods [ 109 , 110 , 111 , 112 , 113 , 114 ], magnetophoretic deposition [ 115 ], centrifugal method [ 96 , 116 , 117 ], and gravity-assisted casting [ 97 ] have been reported to produce FGMs, as discussed below.…”
Section: Anisotropic and Nonlinear Polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional grading methods used in the literature for the fabrication of polymer composites and micro- and nanofillers are liquid-phase processing. Extrusion [ 105 , 106 ], infiltration [ 107 , 108 ], electrical deposition methods [ 109 , 110 , 111 , 112 , 113 , 114 ], magnetophoretic deposition [ 115 ], centrifugal method [ 96 , 116 , 117 ], and gravity-assisted casting [ 97 ] have been reported to produce FGMs, as discussed below.…”
Section: Anisotropic and Nonlinear Polymer Compositesmentioning
confidence: 99%
“…Nardi [ 115 ] et al reported that a suspension of Fe 3 O 4 @TiO 2 nanoparticles in an epoxy matrix induced the magnetophoretic motion of particles and high-aspect-ratio particle alignment under an external magnetic field. The combination of these two effects produces graded nanocomposites with permittivity gradients.…”
Section: Anisotropic and Nonlinear Polymer Compositesmentioning
confidence: 99%
“…In addition to the abovementioned methods, the magnetophoresis and the electrophoresis methods have also been introduced to fabricate FGM. In 2016, Nardi et al [36] prepared FGM samples by applying an external magnetic field on the suspension system of Fe 3 O 4 @TiO 2 nanoparticles and epoxy matrix, as shown in Fig. 8.…”
Section: Bulk Fgm Insulator For Compact Gis/gilmentioning
confidence: 99%
“…Fabricated ɛ-FGM spacer model by FMC[35] Cross-sectional SEM-EDX spectral images showing the Ti content of different samples[36] (a) 2 vol%, (b) 6 vol%, (c) 12 vol%…”
mentioning
confidence: 99%
“…Therefore, nanoparticle gradient materials have big potential for applications in optics, electronics, sensors, and magnetic devices. Recent developments include functionally graded carbon nanocomposites, magnetic particle gradients, and metal nanoparticle gradients at surfaces . Established preparation methods for polymeric gradient composites like centrifugal casting, corona discharge, photopolymerization,selective laser sintering, and 3D printing lack the possibility to simulate the gradients in advance and/or to detect the nanoparticle concentration gradient during processing.…”
mentioning
confidence: 99%